2000
DOI: 10.1128/jb.182.9.2624-2628.2000
|View full text |Cite
|
Sign up to set email alerts
|

The GacS Sensor Kinase Regulates Alginate and Poly-β-Hydroxybutyrate Production in Azotobacter vinelandii

Abstract: Azotobacter vinelandii produces two polymers: the extracellular polysaccharide alginate and the intracellular polyester poly-␤-hydroxybutyrate (PHB). A cosmid clone (pSMU588) from an A. vinelandii gene library diminished alginate production by A. vinelandii mucoid strain ATCC 9046. The nucleotide sequence and predicted amino acid sequence of the locus responsible for the mucoidy suppression revealed 65% identity to Pseudomonas GacS, a transmembrane sensor kinase of the two-component regulators, whose cognate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 34 publications
3
46
1
2
Order By: Relevance
“…6a) and calculations made with  software, as described by Espinosa-Urgel & Tormo (1993), show that the sequence upstream of P1 has intrinsic DNA curvature (data not shown). In support of this hypothesis, it has been shown that algD transcription and alginate formation in A. vinelandii is regulated by GacSA, a sensor kinase that influences RpoS levels in the cell (Castaneda et al, 2000). Similarly, alginate formation in P. aeruginosa is greatly reduced in an RpoS mutant (Suh et al, 1999).…”
mentioning
confidence: 65%
“…6a) and calculations made with  software, as described by Espinosa-Urgel & Tormo (1993), show that the sequence upstream of P1 has intrinsic DNA curvature (data not shown). In support of this hypothesis, it has been shown that algD transcription and alginate formation in A. vinelandii is regulated by GacSA, a sensor kinase that influences RpoS levels in the cell (Castaneda et al, 2000). Similarly, alginate formation in P. aeruginosa is greatly reduced in an RpoS mutant (Suh et al, 1999).…”
mentioning
confidence: 65%
“…16 The regulatory mechanisms for the production of these biopolymers have been analyzed. [16][17][18][19][20][21][22][23][24][25] Thus, the biopolymers are expected to be produced from excess and/or unused resource by A. vinelandii.…”
Section: Introductionmentioning
confidence: 99%
“…These are known under two different names, PhaR and AniA (11,12,28,29,46). In addition, two different types of transcriptional regulators have been reported elsewhere to be involved in PHB production in Azotobacter vinelandii (4,45).…”
mentioning
confidence: 99%